2014
DOI: 10.1042/cs20140089
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs: emerging biomarkers for diagnosis and prognosis in patients with gastrointestinal cancers

Abstract: To identify novel non-invasive biomarkers for improved detection, risk assessment and prognostic evaluation of cancer, expression profiles of circulating microRNAs are currently under evaluation. Circulating microRNAs are highly promising candidates in this context, as they present some key characteristics for cancer biomarkers: they are tissue-specific with reproducible expression and consistency among individuals from the same species, they are potentially derived directly from the tumour and therefore might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 97 publications
0
35
0
Order By: Relevance
“…MiRNAs are closely associated with tumor occurrence and development. Some miRNAs can promote tumor proliferation and metastasis, whereas others inhibit tumorigenesis (Gallach et al, 2014;Lindner et al, 2015). Previous research showed that miRNAs are abnormally expressed in osteosarcoma, and may function as oncogenes or tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are closely associated with tumor occurrence and development. Some miRNAs can promote tumor proliferation and metastasis, whereas others inhibit tumorigenesis (Gallach et al, 2014;Lindner et al, 2015). Previous research showed that miRNAs are abnormally expressed in osteosarcoma, and may function as oncogenes or tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer, they are deregulated and involved in tumorigenesis, tumor progression, metastasis and resistance to treatment. Furthermore, miRNAs have recently been proposed as promising biomarkers for cancer diagnosis and follow-up studies on disease progression, because they can be detected in body fluids, carried by MPs or associated with proteins that protect them from degradation (Fujiwara et al 2014;Inns and James 2015;Jackson et al 2014;Lindner et al 2015;Liu and Xiao 2014;Pimentel et al 2014). Several groups are attempting to uncover the underlying mechanisms involved in miRNA selection, release and transport to blood fluids and their role in cancer (Arroyo et al 2011;Li et al 2012;Turchinovich et al 2011).…”
Section: Microparticles and Micrornasmentioning
confidence: 98%
“…miRNA’s are single stranded, non-coding RNA’s that can regulate gene and protein expression[43,44]. miRNAs are abundantly expressed in a stable form, with highly consistent levels amongst individuals in a range of extracellular fluids including blood serum and plasma, and have drawn attention as biomarkers for cancer and disease[43,44].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…miRNAs are abundantly expressed in a stable form, with highly consistent levels amongst individuals in a range of extracellular fluids including blood serum and plasma, and have drawn attention as biomarkers for cancer and disease[43,44]. Recent studies have reported plasma/serum circulating miRNAs to be potential diagnostic and prognostic markers in some gastrointestinal cancers - esophageal squamous, esophageal adenocarcinoma, gastric and colorectal[43,44]. Although still an emerging area of research, recent meta-analyses have highlighted the potential of circulating miRNAs for the detection of esophageal cancer.…”
Section: Circulating Mirnamentioning
confidence: 99%